Masking The Meaningful. (May 2016) - Kitcher, Philip
Abstract: There are obvious reasons why citizens of the nations we mark out as democracies fail to support policies that address catastrophic threats. The current condition of many such nations allows for marked differences between preferences and interests (to the extent that the choice of the label 'democracy' can be seriously questioned). Failures in the transmission of crucial information are intensified because of market competition among media sources and widespread difficulties in understanding issues couched in terms of probabilities. Beyond these, however, are prevalent social conditions that interfere with citizens' abilities to discern their interests. I suggest an account of the notion of interests (and of the related concept of freedom) in terms of an environment that provides opportunities for reflective choice. Such environments are highly vulnerable, and political and economic institutions within 'democratic' nations can systematically destroy them. Throughout, I use the example of responses to climate change to illustrate my claims. Abstract : Capitalism in its present form is not the promoter of freedom its champions proclaim, but rather a direct threat to it. It also makes the hardest problem of climate change insoluble.